Circulating Adipokines and Response to Treatment in Patients With Early Rheumatoid Arthritis - Georgios K. Vasileiadis; Yuan Zhang; Tahzeeb Fatima; Ronald van Vollenhoven; Jon Lampa; Bjorn Gudbjornsson; Espen A. Haavardsholm; Dan Nordström; Gerdur Grondal; Kim Hørslev‐Petersen; Kristina Lend; Marte S. Heiberg; et al. (ACR Open Rheumatology)
Objective The objective of this study was to determine if baseline adiponectin, leptin, and resistin levels are associated with response to antirheumatic treatment in early rheumatoid arthritis (RA). Methods This study included 341 participants of the Nordic Rheumatic Diseases Strategy Trials and Registries trial with untreated early RA, randomized at baseline into four treatment arms: methotrexate combined with (1) prednisolone, (2) certolizumab, (3) abatacept, or (4) tocilizumab. Follow‐up was up to 48 weeks. Adipokines were measured in plasma at baseline with enzyme‐linked immunosorbent assay. The primary outcome for this report was the difference in remission (Clinical Disease Activity Index [CDAI] ≤2.8) over 48 weeks stratified by median adipokine levels. Results At baseline, levels of adiponectin and leptin were not associated with markers of RA activity, whereas participants with higher resistin levels had higher C‐reactive protein (CRP) levels, swollen joint count, and Disease Activity Score in 28 joints based on CRP compared to participants with lower resistin. Overall, participants with baseline adipokine levels above the median and those with adipokine levels below the median had similar mean CDAI and changes in CDAI throughout follow‐up for up to 48 weeks. Adjusted Cox proportional hazards models did not show any effect of baseline adiponectin, leptin, and resistin levels on the likelihood of achieving CDAI remission (adiponectin: hazard ratio [HR] 1.08, 95% confidence interval [CI] 0.80–1.45, P = 0.62; leptin: HR 0.89, 95% CI 0.64–1.26, P = 0.52; resistin: HR 0.86, 95% CI 0.65–1.13, P = 0.26). Conclusion Baseline adiponectin, leptin, and resistin levels are not associated with the likelihood of achieving CDAI remission over 48 weeks of treatment in a large cohort of people with untreated early RA.